A History of the “Thieves in Law” - Alexandru PARENIUC; Andrei NASTAS (ACROSS)
The article includes a brief analysis of the historical premises for the appearance and development of criminals with their criminal status of "thief in law/ outlaw" through special investigative activity. At the same time, the appearance and history of this dangerous phenomenon, processes, and criminal traditions are reviewed. The conclusions, with which the authors intervene through modest research, will complete the arsenal of investigative ideas of criminal investigation officers and investigation officers in carrying out the tasks, stages and phases of the criminal and special investigation process.